2005
DOI: 10.1016/j.orthres.2005.02.017.1100230602
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-KB signalling and TNFα-expression in THP-1 macrophages by TiAlV- and polyethylene-wear particles

Abstract: Wear particles are believed to induce periprosthetic inflammation which contributes to periprosthetic osteolysis. TNFu plays a pivotal role in the pathogenesis of this process. The molecular mechanisms leading to the development of periprosthetic inflammation with upregulated TNFa expression in monocytic cells in response to different wear particles have yet to be defined. 1n:this study we evaluated the effects of polyethylene-and TiAIV-particles on activation of NF-KB signalling pathways and TNFa biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Immediately after this activation, the cells were incubated with the particles in a rotational device with the risk that the cells would still be influenced by these mediators, which are capable of affecting RANKL and OPG expression 17, 18. However, some authors are of the opinion that macrophages entering periprosthetic tissue might already be activated and that the way in which Baumann et al19 stimulated their cells could simulate physiological conditions. Some modifications have been made in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after this activation, the cells were incubated with the particles in a rotational device with the risk that the cells would still be influenced by these mediators, which are capable of affecting RANKL and OPG expression 17, 18. However, some authors are of the opinion that macrophages entering periprosthetic tissue might already be activated and that the way in which Baumann et al19 stimulated their cells could simulate physiological conditions. Some modifications have been made in our study.…”
Section: Discussionmentioning
confidence: 99%
“…LPS was reconstituted in DPBS and stored at -20°C until use. During the experiments, LPS was administered to macrophage-like cells at a final concentration of 1 µg/ml [43]. …”
Section: Methodsmentioning
confidence: 99%
“…Baumann and colleagues, 15 using the human monocytic leukemic cell line (THP-1) showed both PE and prosthesis-derived titanium aluminum vanadium (TiAlV) particles induced a significant release of TNF-α after 6 hours of exposure (17-fold for TiAlV and 15-fold for PE, all p < 0.05) and a significant upregulation of RANK mRNA (3.5-fold increase for TiAlV p = 0.040 and 3-fold increase for PE, p = 0.040). They found that OPG mRNA expression was transiently upregulated after exposure to PE and TiAlV particles.…”
Section: Reviewmentioning
confidence: 99%